2019
DOI: 10.1002/1878-0261.12465
|View full text |Cite
|
Sign up to set email alerts
|

New clinical trial designs in the era of precision medicine

Abstract: Cancer treatment has made significant strides towards the promise of personalized medicine. Recent scientific advances have shown that there are numerous genetic deregulations that are common in multiple cancer types, raising the possibility of developing drugs targeting those deregulations irrespective of the tumour type. Precision Cancer Medicine (PCM) was born out of accumulated evidence matching targeted agents with these tumour molecular deregulations. At the same time, the therapeutic armamentarium is ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 38 publications
0
88
0
Order By: Relevance
“…CIViC database [78,149] OncoKB database [77,150] Standards and guidelines for the interpretation and reporting of sequence variants in cancer [86] MAP [163,164]. A number of basket trials around the world are currently recruiting patients, some of which are highlighted in Table 4.…”
Section: Variantmentioning
confidence: 99%
“…CIViC database [78,149] OncoKB database [77,150] Standards and guidelines for the interpretation and reporting of sequence variants in cancer [86] MAP [163,164]. A number of basket trials around the world are currently recruiting patients, some of which are highlighted in Table 4.…”
Section: Variantmentioning
confidence: 99%
“…Identifying those molecular features has led to a clinical strategy in which testing upfront or after first-line failure may provide certain novel therapeutic opportunities. In umbrella trials, patients diagnosed with the same type of solid tumors are treated according to their molecular features, while in basket trials, patients diagnosed with different types of solid tumors with a common driver molecular alteration are selected and treated with a specific inhibitor [36]. As an example, a multisite study (including >1000 patients with non-small cell lung cancer) showed that matching was associated with longer survival than was seen in patients without genotype-directed treatment.…”
Section: The Revolution Of Tumor Treatment: From Tumor Site To Molecumentioning
confidence: 99%
“…commercial/financial consequences [2]. An evolution has started towards more innovative, efficient and adaptive trial designs [39], built around active participation of patients and patient organisations. Adaptive clinical trials, irrespective of the trial phase, use the results accumulated in the trial to modify the trial's course in accordance with pre-specified rules [40].…”
Section: … To Innovation In Regulation and Businessmentioning
confidence: 99%